Assessment of different isotope dilution strategies and their combination with switchable solvent-based liquid phase microextraction prior to the quantification of bisphenol A at trace levels via GC-MS - Bodur, Suleyman; Erarpat, Sezin; Chormey, Dotse Selali; Bozyigit, Gamze Dalgic; Oz, Ersoy; Ozdogan, Nizamettin; Bakirdere, Sezgin (ROYAL SOC CHEMISTRY, 2020)
In this study, a novel analytical method was developed for the determination of trace level bisphenol A (BPA) in bottled water and wastewater samples. Switchable solvent-based liquid phase microextraction (SSLPME) was combined with quadrupole isotope dilution (ID4) to improve the accuracy/precision and lower the detection limit. In the first step of this study, double isotope dilution (ID2), triple isotope dilution (ID3), quadrupole isotope dilution (ID4), standard addition-double isotope dilution (SA-ID2) and standard addition-triple isotope dilution (SA-ID3) were applied for the determination of BPA to check their effectiveness in terms of accuracy and precision. ID(4)was selected as the best strategy to quantify the analyte. In order to improve the detection power, a microextraction strategy was adopted for the system and the developed combination called SSLPME-ID4-GC-MS was successfully applied for the trace quantification of BPA. Under the optimum conditions, percent recovery results were calculated as 99.4 +/- 0.7% and 99.9 +/- 0.8% for bottled water and wastewater samples spiked with BPA at 223.8 and 169.9 ng g(-1), respectively.
Keywords: ELEMENTAL SPECIATION; SENSITIVE DETECTION; MASS-SPECTROMETRY; WASTE-WATER; CHROMATOGRAPHY; EXTRACTION; NANOPARTICLES; OPTIMIZATION; OCTYLPHENOL; PRINCIPLES; Chemistry